O circuito espacial de produção do vestuário: os usos do território do Rio Grande do Norte no contexto técnico-científico-informacional - Farias, Francisca Diane Pereira de (2021)
The technical-scientific-informational period amplified the possibilities for expansion and command of capitalist economic activities at a global level. In this context, the modernization of the telecommunications and transport systems has become the tools that enabled the increase of material and immaterial flows and the widening of the territorial division of labor, in addition to the new role that financialization and credit have taken on in the context of world economy.In Brazil, this process intensifies since 1970, which made it possible to deepen the territorial division of labor at a national level and to expand and emerge new spatial production circuits. In this context, new forms of use of the territory in Rio Grande do Norte were created by the hegemonic agents of the economy, in line with the actions of the State. Therefore, a process of restructuring of its territory and of the pre-existing economic activities was promoted, among them, the textile industry of clothing and apparel, which started to be commanded by large companies originated, mainly, in the Southeast of the country. Regarding specifically the clothing sector, there is the configuration of a wide and diverse spatial production circuit, in terms of agents, scales, networks and material and immaterial flows. In this way, the thesis here defended starts from the premise that, the diffusion of the technical-scientific-informational medium in Brazil and the incentive policies to industrial development promoted by the State, expanded and diversified the spatial circuit of clothing production in Rio Grande do Norte from the increase in the flow of goods, the attraction of large external economic groups, the creation of medium and small local companies and the territorial expansion on a national scale of the Guararapes Group. Therefore, we aimed to understand how the use of potiguar territory is configured by the spatial circuit of clothing production in the technical-scientific-informational context. To this end, the study is based on the theoretical-methodological conception of spatial circuits of production and on the contributions of several interlocutors, among which the geographer Milton Santos stands out, in addition to other authors who expand the reflection on the current global economic situation, such as David Harvey, François Chesnais, Georges Benko and others. The results obtained confirm the thesis presented that the process of productive restructuring, the diversification of the technical-scientific-informational environment in line with financialization allowed for different ways of using the territory of Rio Grande do Norte by the spatial circuit of clothing production. The performance of small local capital companies such as Del Rayssa, Daya, Miss Modas and others, present strategies for organizing and expanding the stages of production, circulation and trade subsidized by elements inherent to this process, however, the scale of action of these agents is circumscribed to the local and regional dimensions, presenting varying levels with regard to the technical content employed and the incorporation of the variables resulting from financialization, which makes it difficult, among other factors, to expand its scales of territorial realization. On the other hand, companies with national operations, such as the Guararapes Group, have expanded their territorial participation in the space production circuit of clothing, based on the articulation between policies to encourage industrialization promoted by the State, the adoption of productive flexibility, the tools of the environment technical-scientific-informational for the rational and logistical use of the state and national territory, and the association between industrial, commercial and financial capital.